Inovasi Pembelajaran: Pengembangan Eco-Explorer Game Terintegrasi SDGS Terhadap Dimensi Bergotong Royong dan Hasil Belajar Kognitif - Juwita Oktaviani; Mimien Henie Irawati Al-Muhdhar; Sofia Ery Rahayu; Sueb Sueb; Deny Setiawan; Wachidatul Linda Yuhanna; Nunik Hidayati; Muhammad Iqbal Akbar (Jurnal Inovasi Pembelajaran Biologi, 2026)
Learning ecosystem material can be taught in line with efforts to realize the Sustainable Development Goals, one of which is the point of Life on Land. Learning media plays a crucial role in facilitating effective learning and offers advantages, especially in terms of flexibility and interactivity. This development aims to produce a website-assisted learning product, the Eco-Explorer Game, which is effective in improving the dimensions of mutual cooperation and cognitive learning outcomes. The development process follows the Lee & Owens model, which consists of five stages: analysis, design, development, implementation, and evaluation. In the implementation stage, this study used a pre-experimental design with a one-group pretest-posttest technique, with a sample consisting of 36 tenth-grade students at SMAN 1 Singosari. Quantitative data were collected through two main instruments: pretest and posttest scores to measure cognitive learning outcomes, and observation sheets equipped with a quantitative assessment rubric to measure the dimensions of mutual cooperation (collaboration, caring, and sharing). The data analysis technique to measure the improvement of both variables used the N-Gain test. The collected data shows that the game is proven to be effective in improving the dimensions of mutual cooperation and students' cognitive learning outcomes as indicated by the increase in the average achievement results of each indicator both in the dimensions of mutual cooperation (from the initial 56.1 to 88.7) and also cognitive learning outcomes (from the initial 66.8 to 87.7). The N-Gain score obtained from the observation sheet for the dimensions of mutual cooperation shows a high score of 0.7. Furthermore, cognitive learning outcomes show an N-Gain score of 0.62, which is included in the moderate category. Based on these findings, it can be concluded that the Eco-Explorer Game is very effective in improving the dimensions of mutual cooperation of students and is quite effective in improving their cognitive learning outcomes.